Peningkatan Mutu Pendidikan Melalui Manajemen Perpustakaan Di MIS Muhammadiyah Sibatua Kabupaten Pangkep - M. Aris Akin; Nurkhadijah Nurkhadijah; Ashabul Kahfi (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Management is a process of achieving planned, organized and oversight goals of all organizational activities to improve the quality of education that houses the school, the library as an institution that manages key sources of information in the educational process which helps improve the quality of education. Libraries as learning resources require good and professional management. The purpose of this research is to find out how library management improves education management at SMP Negeri 1 Delima, and to find out how to improve the quality of education through library management at MIS Muhammadiyah Sibatua, Pangkep Regency. This study used a qualitative method with a descriptive approach, while the subjects in this study were school principals, teachers and school librarians. Data collection techniques in this study used observation, interviews and documentation. The results showed that library management in improving the quality of school education. library work program, the third is making a library development program which consists of developing human resources, institutional development, and developing library infrastructure, then the fourth stage is planning library evaluation activities.